Solid particle distribution in particle-laden turbulent channel flows. (26th November 2008) - Lei, Kang-Bin; Kase, Kiwamu; Oshima, Nobuyuki; Kobayashi, Toshio
Large Eddy Simulation (LES) of fully developed particle-laden turbulent channel flows were performed at Reynolds number 180 and 644, respectively. The effects of Stokes numbers, turbulent flows SGS fluctuations and inter-particle collisions on the distributions of solid particles were discussed. It was verified that, regardless of the Reynolds number of fluid flows, the maximum departure from randomness is when the ratio of the particle's aerodynamic response time to the Kolmogorov time scale of flow was approximately one. In addition, the simulation results showed that the degrees of particle preferential concentration are selectively associated with the SGS fluctuations of fluid turbulence.